Pengaturan Penggabungan Gugatan Wanprestasi dan Perbuatan Melawan Hukum - Rachmadhanto, Dimas Adam Satrio; Permatasari, Rika; Anjawai, Namrysilia Buti; Simanjuntak, Fhlorida Agustina (AL-SULTHANIYAH, 2026)
Civil litigation practice in Indonesia demonstrates a tendency for plaintiffs to combine claims of breach of contract and tort (unlawful act) within a single statement of claim. This combination gives rise to juridical debate, as breach of contract and tort are grounded in distinct conceptual foundations within civil law. This study aims to analyze the joinder of such claims from the perspectives of legal ontology, epistemology, and axiology. The research employs a normative legal method, utilizing both conceptual and case approaches. The findings indicate that, ontologically, breach of contract and tort constitute two distinct legal entities; however, from an epistemological standpoint, their combination may be justified insofar as it is based on a single sequence of legal events. From an axiological perspective, the joinder of claims can promote utility and justice for the parties, although it also carries the potential to create legal uncertainty if not carefully formulated.